Evaluation of Enrofloxacin Sensitivity on Free and Biofilm Form of Salmonella Pullorum - Kavitha; Chandrakala, G.K.; Byregowda, S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
In the present study, Enrofloxacin sensitivity of free/planktonic and biofilm forms of Salmonella Pullorum was assessed for a period of 20 days. The parameters like Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Biofilm Elimination Concentration (BEC) were evaluated. The investigation revealed that the MIC and MBC values for biofilm form were found to be slightly higher than planktonic form. The values of MIC and MBC of enarofloxacin against planktonic as well as biofilm forms of S. Pullorum were found non significant (P>0.05) during the study period. The BEC values obtained were found higher than the MBC values. Hence, the findings suggested that the fluroquinolone antibacterial drug, enrofloxacin was found effective against the planktonic and biofilm forms of S. Pullorum and can be used for its management.